Future Prevention of Coronary Artery Disease Based on Genetic Risk Stratification - Roberts , Robert; Luna , Esperanza Acuna; Roberts , Alison MacKenna (Research Highlights in Disease and Health Research Vol. 1, 2023)
The risk for Coronary Artery Disease (CAD) is estimated to be 50% genetic and 50% acquired. Acquired risk factors are well known and decreasing their risk, such as cholesterol, decreases cardiac mortality and morbidity, many, however, do not develop until the 6th or 7th decades, precluding primary prevention. The first genetic risk variant for CAD was discovered in 2007 and over 200 have since been discovered. Using genetic risk variants to predict one’s risk for CAD has been validated in 1 million individuals. Clinical trials show genetic risk is reduced by decreasing plasma cholesterol and lifestyle changes. The genetic risk factors predisposing to CAD, in contrast, are not age dependent being present at conception and do not change throughout one’s lifespan. Thus, genetic risk stratification is possible early in life even at birth if necessary. Secondly, the availibilty of the PRS enables one for the first time to provide comprehensive risk stratification for CAD utilizing both conventional and genetic risk factors. Thirdly, while the Current Cardiology Clinical Practice Guidelines do not include the PRS they encourage the use of other factors that would enhance risk stratification. The example mentioned in the CCCPG is the calcium score. It is expected that furture guidelines would include primary prevention of CAD based on PRS stratification. Fourthly, early genetic risk stratification enables early primary prevention. This would be a paradiagm shift in the prevention of CAD, the most common cause of morbidity and mortality in the world. Lastly, the PRS will continue to improve and with the continuing search for additional DNA risk variants will become more applicable to other ethnic groups, as well as provide new targets for development of novel drugs.